Design and Application of Risk Management in Public Accounting Firm (KAP) - Veronica, Veronica; Yuwono, Wisnu (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
This study aims to design and implement risk management in Public Accounting Firms (KAP). This research combines field research and literature research. This research uses a qualitative approach and utilizes descriptive data from interviews and brainstorming to obtain field data. Literature research uses literature studies and previous research. The process of designing and implementing risk management starts from risk identification, risk analysis, risk evaluation, and risk treatment. The results of risk identification show that KAP has several risks that can result in complaints from clients, audit delays, wrong opinions, and financial losses. Risk analysis shows that 3 events are at the medium priority level and 2 events are at the low priority level. A risk evaluation was conducted and showed that 5 risk events actually at medium priority. Finally, risk response analysis shows that risks can be mitigated by mitigation and avoidance. Researchers recommend KAP and similar companies to consistently apply risk management in the audit process so that companies can reduce the adverse effects of risks or take advantage of risks in a direction that benefits the company.